Revisiting the Mechanism of Hydrolysis of Betanin1. (15th March 2018) - Esteves, Larissa C.; Pinheiro, Amanda C.; Pioli, Renan M.; Penna, Tatiana C.; Baader, Wilhelm J.; Correra, Thiago C.; Bastos, Erick L.
Abstract: Betanin (betanidin 5‐ O ‐β‐D‐glucoside) is a water‐soluble plant pigment used as a color additive in food, drugs and cosmetic products. Despite its sensitivity to light and heat, betanin maintains appreciable tinctorial strength in low acidic and neutral conditions, where the color of other plant pigments, such as anthocyanins, quickly fades. However, betanin is an iminium natural product that experiences acid‐ and base‐catalyzed hydrolysis to form the fairly stable betalamic acid and cyclo ‐DOPA‐5‐ O ‐β‐D‐glucoside. Here, we show that the decomposition of betanin in aqueous phosphate solution pH 2–11 is subject to general base catalysis by hydrogen phosphate ion and intramolecular general acid and base catalysis, providing new insights on the mechanism of betanin hydrolysis. UV/Vis absorption spectrophotometry, 1 H NMR spectroscopy and mass spectrometry were used to investigate product formation. Furthermore, theoretical calculations support the hypothesis that the nitrogen atom of the tetrahydropyridine ring of betanin is doubly protonated, as observed for structurally simpler amino dicarboxylic acids. Our results contribute to the study of betanin and other pigments belonging to the class of betalains and to deepen the knowledge on the chemical properties of imino acids as well as on iminium‐catalyzed modifications of carbonyl compounds in water. Abstract : The mechanism of betanin decomposition in aqueous solution as a function of pH and temperature is investigated. Results are of importance for the application of betanin, other betalains and iminium ions.